2002
DOI: 10.1515/znc-2002-7-811
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Tyrolobibenzyl D and Biological Activity of Tyrolobibenzyls from Scorzonera humilis

Abstract: A novel tyrolobibenzyl derivative, 1→6-β-ᴅ-apiosyl-β-ᴅ-glucopyranosyl 4-[2-(4-hydroxyphenyl) ethyl]benzofuran-2-carboxylate 3 (tyrolobibenzyl D) was isolated from Scorzonera humilis L. and its structure established by mass spectrometry and 1D- and 2D-NMR spectroscopy. The biological activities of the new compound and related tyrolobibenzyls A-C (1-2, 4) and the semi-synthetic peracetyl derivatives of tyrolobibenzyls B (2a) and C (4a) were assessed. The results revealed no cytotoxic activity against P388 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Better results were found for petroleum ether fraction. Another study of S. humilis L. reported that no antibacterial activity against Bacillus subtilis and nor antifungal activity against Candida albicans wasn't found (Zidorn et al, 2000;Zidorn et al, 2002). As reported Erden and Kirbağ (2015), three species of genus of Scorzonera showed antimicrobial effect on Escherichia coli (17-27 mm of inhibition zone) and none of the plant extracts showed any effect against Klebsiella pneumoniae.…”
Section: Tablementioning
confidence: 93%
“…Better results were found for petroleum ether fraction. Another study of S. humilis L. reported that no antibacterial activity against Bacillus subtilis and nor antifungal activity against Candida albicans wasn't found (Zidorn et al, 2000;Zidorn et al, 2002). As reported Erden and Kirbağ (2015), three species of genus of Scorzonera showed antimicrobial effect on Escherichia coli (17-27 mm of inhibition zone) and none of the plant extracts showed any effect against Klebsiella pneumoniae.…”
Section: Tablementioning
confidence: 93%
“…It was reported that the pilatifillozide compound was isolated from the cytotoxic activated directed study of S. pseudodivaricata plant [15]. The cytotoxic activity of thyrolobibenzyls obtained from S. humilis, antibacterial activity against P-388 cells, and antifungal activity against Candida albicans and Trichophyton mentagrophytes were investigated, but it was reported that the compounds showed no activity [18,23]. According to the best of our knowledge, there is no any secondary metabolite isolation, structure determination and biological activity studies with S. aucheriana, which we plan to work.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the Scorzonera genus are used as vegetables and medicinal plants. Phenolic compounds such as dihydroisocoumarins [ 2 , 3 ], bibenzyl derivatives [ 4 , 5 , 6 ], flavonoids [ 7 , 8 , 9 ], lignans [ 6 , 10 ], stilbene derivatives [ 11 ], quinic and caffeic acid derivatives [ 8 , 12 ], sesquiterpenes [ 4 , 8 , 13 ] and triterpenes [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ] have been isolated from Scorzonera species. Triterpenes are one of the largest groups of terpenes [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%